A mapping forwarding approach for supporting mobility in networks with identifier/locator separation. (16th November 2011) - Qiu, Feng; Luo, Hongbin; Li, Xiaoqian; Xue, Miao; Dong, Ping; Zhang, Hongke
SUMMARY The identifier/locator separation has been widely recognized as a feasible solution for addressing the current Internet's routing scaling problem. Moreover, such a separation solution in terms of mobility can keep connection survivability and support global seamless roaming. A critical challenge in supporting efficient mobility is how to update the identifier‐to‐locator mappings of mobile nodes (MNs). In this paper, we propose a mapping forwarding (MF) scheme for location management in the identifier/locator separation architecture. In the MF scheme, a tunnel router (xTR) is selected as an agent of an MN and keeps the MN's identifier‐to‐locator mapping invariable by setting up an MF chain. As long as the MN is managed by the same xTR, the MN's mapping stored in the xTR of each correspondent node of the MN does not need to be updated, thus reducing the location update signaling cost. Meanwhile, the unchanged mapping assures the correct forwarding of packets, which reduces mobility‐related disruption and enhances the location management's reliability. In addition, for the handoff in two MF chains, we propose a data‐triggered update scheme that can achieve route optimization. To evaluate the proposed MF scheme, we establish two analytical models and formulate the blocking probability and the total protocol cost. The performance results show how the blocking probability changes under various parameters and how the MF scheme can effectively reduce the blocking probability compared with the location management scheme without the MF strategy. Meanwhile, our analysis demonstrates that the MF scheme has a lower overhead when the mobility rate is high. Copyright © 2011 John Wiley & Sons, Ltd.